Measuring Aesthetics of Mandarin Learning Web Pages: Are User's Perceptions Congruent with Aesthetics-Measurement Application (AMA) - Tey, Meng Kar; Jasni, Mohamad Zain; Goh, Yin Soon (2007)
Aesthetics of web pages refers to how attractive a web page is in which it catches the attention of the user to read through the information. Visual appearance is important in getting attentions of the users. It was found that there is a positive correlation between the aesthetic aspects and the perceived usability of Virtual Learning Environments (VLE) interfaces [6]. It was also found that those screens which were perceived as aesthetically pleasing were having a better usability [7]. It is thus suggested that the more aesthetic a web page is, the more useful the web page can be. Therefore, the measurement of aesthetics can be viewed as an important task that should not be disregarded. For this research, the positions of objects, images element and texts element are defined as objects in a multi screen interface and are measured. Mandarin learning web pages used in this research comprised of main pages, learning pages and exercise pages, on the first author’s E-portfolio web site. The web pages were manipulated according to the desired aesthetic values. The six aesthetics related elements used are balance, equilibrium, symmetry, sequence, rhythm, as well as order and complexity. On top of it, questionnaires were distributed to the users to gather information on the students’ perceptions on the aesthetic aspects. Respondents for this study were students taking Mandarin course level I at UiTM Terengganu. It was found that the users’ perceptions were congruent with the aesthetics values measured by using our self-developed Aesthetics-Measurement Application (AMA). Hence, our AMA perhaps can be introduced as an effortless tool for web page aesthetics measurement.